Optimalisasi digital marketing untuk meningkatkan pasar UMKM JakPreneur wilayah Jakarta Timur - Gatot Prabantoro; Rimi Gusliana Mais; Megayani Megayani; Maya Mustika; Preztika Ayu Ardheta; Hendryadi Hendryadi (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
This activity aims to answer the needs of MSMEs in the normal era of Covid-19, namely the digitalization of business marketing development. The target of this activity is MSME players in the East Jakarta area, including the community from several sub-districts that are members of the Jakpreneur UMKM East Jakarta Region, namely Jatinegara District, Matraman District, Cakung District, Pulo Gadung District, Duren Sawit District, Pondok Kopi District with various business fields ranging from culinary, fashion, services and other creative industries. The method for carrying out this activity was an offline workshop with 109 participants at the East Jakarta Mayor's Office Block D Building. Assistance in digital marketing using Google My Business to expand the reach and attractiveness of business information for East Jakarta JackPreneur MSMEs. To evaluate this activity, pre-tests and post-tests were carried out, and it was found that the results of this socialization provided increased awareness to MSME actors (up 42% from 12% to 54%) of the importance of digitalization in informing businesses in the digital era, to improve MSME business performance.